Asset-based learning and the pedagogy of community development. Issue 3 (27th May 2017) - Missingham, Bruce D.
Abstract: This article argues that much community development education in universities is still very conventional, lecturer-centered, and based on deficit assumptions about students' knowledge and experience. Nevertheless, education and learning processes are central concerns of the discipline of community development, and we need to reflect critically on the pedagogy of community development. The article argues that Asset-Based Community Development and critical pedagogy, both influential bodies of theory and practice in our discipline, stand to make important contributions to developing an applied critical pedagogy of community development in higher education.